Fat content and EPA and DHA levels of selected marine, freshwater fish and shellfish species from the east coast of Peninsular Malaysia - Wan Rosli, W. I.; Rohana, A. J.; Gan, Siew Hua; Noor Fadzlina, H.; Rosliza, H.; Helmy , H.; Mohd Nazri, S.; Mohd Ismail , I.; Shaiful Bahri, I.; Wan Mohamad, W. B.; Kamarul Imran, M. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The total lipid contents and the concentration of eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acid of fourteen selected marine, three freshwater fish species, four shellfish species and two selected canned fish species of East Coast of Peninsular Malaysia were determined. The fat content of all samples ranged from 1.01 % to 15.83 % with silver catfish reported to have the highest value. Most of the fish had fat amounts lower than 10% of their total weight. In general, DHA concentrations (50.50-165.21 μg/g) were significantly higher than EPA (11.12-55.38 μg/g) in all of the fish species analyzed. Among all marine fish species, the sixbar grouper recorded the highest concentration of DHA (165.21 μg/g) while barramundi had the highest concentration of EPA (55.38 μg/g). In conclusion, all fish and shellfish species are considered a good source of EPA and DHA, representing a very valuable essential nutrient for maintenance of human health.